2009
DOI: 10.1007/s00431-009-0922-3
|View full text |Cite
|
Sign up to set email alerts
|

Late onset subgaleal hemorrhage infection with Streptococcus pneumoniae?

Abstract: We report a case of an infected subgaleal hematoma caused by an unusual micro-organism in a previously healthy 11-month-old girl. Our patient presented at the emergency department with an increasing scalp swelling for 2 weeks, and culture of the evacuated fluid yielded Streptococcus pneumoniae. Although she was born after vacuum delivery and a scalp swelling was noticed from the third day of life, this swelling disappeared completely at the age of 3 months. Parents were thoroughly questioned but we could not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In all previously described cases, needle aspiration is performed and aspirate contents sent for Gram stain/ culture. This is often followed by surgical drainage, as occurred in our patient [6,11,25,26] . The choice for operative drainage should be carefully considered, as it may remove the tamponade effect of the surrounding tissues on the hematoma leading to additional hemorrhage into the adjacent subgaleal space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all previously described cases, needle aspiration is performed and aspirate contents sent for Gram stain/ culture. This is often followed by surgical drainage, as occurred in our patient [6,11,25,26] . The choice for operative drainage should be carefully considered, as it may remove the tamponade effect of the surrounding tissues on the hematoma leading to additional hemorrhage into the adjacent subgaleal space.…”
Section: Discussionmentioning
confidence: 99%
“…Pollack et al [11] reported an infected SGH that presented 6 days after vacuum delivery with a polymicrobial flora. Slap et al [25] reported an SGH infected with S. pneumoniae 11 months after a vacuum delivery and temporally associated with otitis media. Ogunrinde et al [26] reported a 9-day-old baby delivered at home who presented to the hospital with an enlarging scalp hematoma without signs of skin breakdown.…”
Section: Discussionmentioning
confidence: 99%